Lifestyle Modifications for Migraine Management - Agbetou, Mendinatou; Adoukonou, Thierry (Frontiers in Neurology, 2022)
Migraine is a disabling disease with a heavy burden for those who suffer from it. Huge advances are being made in the pathophysiological understanding and treatment of the disease. The role of lifestyle modification is more and more preponderant. We have reviewed the current data available on the role of a healthy lifestyle in the management of migraine. Physical activity, the fight against obesity, a good diet and a better lifestyle such as best sleep and avoidance of drug abuse contribute significantly to reducing the frequency and the severity of attacks. It is important to take them into account in the overall management strategies for migraine sufferers.